Escherichia coli contamination of pork carcasses in UK slaughterhouses - Wei, Shao-Hung (2013)
Despite the HACCP systems which have been introduced to the pork industry, cross-contamination which occurs within pork slaughterlines remains an important concern for food safety of the final carcass. The aim of this work was to understand the dissemination and cross-contamination of enteric bacteria during slaughter processing by investigating Escherichia coli populations. E. coli is widely used as an indicator of faecal or enteric pathogen contamination, and a strong correlation between the presence of Salmonella and E. coli levels was seen in this study. With microbiological counts and molecular typing of E. coli, changes of contamination levels as well as of the bacterial communities was observed during processing. The results demonstrated that temperature variation at different carcass sites during the singeing process allowed strains to survive on the cooler sites of the carcass and be present in the subsequent processing stages. The polishing process was recognised as an important site of cross-contamination not only because of an increase in contamination levels but also because a high variety of sources contributed contamination at this site, including strains surviving through singeing, strains that persist in the polisher overnight and strains from faecal leakage during the polishing process. A high percentage of virulence factor-carrying E. coli were present on the slaughtered carcasses and recombination between virulence genes from different pathovars was observed. These findings suggest carcasses slaughtered from a healthy pig herd may still be a potential source for E. coli pathovars in the food chain.